Association of DPP4 with esophageal stricture progression and the Hippo‐ YAP pathway - Rui Wu; Chen Wang; Hui‐Min Tao; Jin Huang; Wei‐Qin Li; Zhi‐Ning Fan (Animal Models and Experimental Medicine, 2026)
Abstract Background Esophageal stricture (ES), a common complication after endoscopic submucosal dissection (ESD), is the consequence of excessive fibrosis and scar formation. The fibroblast‐to‐myofibroblast differentiation is a key characteristic in the pathogenesis of ES, but the molecular basis remains poorly understood. Methods According to the human transcriptome sequencing analysis, which utilized different expression gene analysis and weighted gene co‐expression network analysis, the potential gene associated with ES was explored. Furthermore, we utilized the rat model of ES and the temporal progression of ES after drug treatment to elucidate the role of DPP4 in ES. Subsequently, we identified a significant association between DPP4 and the progression of ES. Finally, we validated our conclusions through experiments on Bama pigs. Results DPP4 expression was consistently elevated in both human ES tissues and the rat ES model. Upon inhibition of DPP4, the proliferative activity of ES primary cells and the expression of fibrosis‐related genes were markedly suppressed. In rats, treatment with a DPP4 inhibitor significantly alleviated ES, which was accompanied by a significant reduction in collagen content and downregulation of fibrosis‐related targets. These effects were observed in conjunction with changes in the Hippo‐YAP pathway, although the data primarily support a parallel association rather than a hierarchical regulatory relationship between DPP4 and this pathway. Conclusions Our findings suggest that DPP4 may contribute to the remodeling of the regenerative microenvironment in ES, with its expression and function occurring in parallel with alterations in the Hippo‐YAP pathway. Direct mechanistic evidence establishing a linear upstream–downstream relationship between DPP4 and Hippo‐YAP signaling remains to be further elucidated.